Rapidly enlarging giant facial mass: Initial presentation of blastic plasmacytoid dendritic cell neoplasm - Gulsen Akoglu; Sibel Orhun Yavuz; Aydan Kilicarslan; Tekin Guney (Our Dermatology Online, 2017)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and aggressive hematological malignancy characterized by proliferation of plasmacytoid dendritic cell precursors. Herein, we describe a 65-year-old male presented with a 6 month history of a progressively enlarging purple mass over his forehead. The histopathological examination revealed non-epidermotropic, dermal, and subepidermal homogeneous infiltration with moderate-sized cells resembling lymphoblasts or myeloblasts. The neoplastic clone diffusely stained positive with CD4 and CD56. They were negative for CD3, CD20, pax-5, CD30, myeloperoxidase, and TdT. Rearrangement studies for T and B cell receptor were negative. Ki-67 proliferation index was 80%. Involvement of multiple lymph nodes was detected. Bone marrow biopsy was normal. The patient was put on six cycles of R-CHOP chemotherapy which was successfully cleared all lesions. A rapid recurrence was observed after 1.5 months. While being prepared for autologous stem cell transplantation, the patient died due to rapidly onset myelosuppression and systemic infections. In conclusion, BPDCN should be in the clinical and histopathological differential diagnosis of rapidly developing tumoral cutaneous lesions. Early diagnosis is important to initiate aggressive treatments in BPDCN, in which skin involvement is very frequent.